Pelatihan Pembangunan Toilet Sehat Untuk Masyarakat Desa Klitih, Kecamatan Plandaan, Kabupaten Jombang - Suharso, Akbar Bayu Kresno (Universitas Wijaya Kusuma Surabaya, 2023)
Community service is a means for universities to contribute and participate in increasing the potential of community life. This is done to socialize technology resulting from research innovations in accordance with their respective scientific fields. This technological knowledge is an alternative solution to the problems faced by rural communities, especially in Klitih Village, Plandaan District, Jombang Regency. The problem is in the form of inadequate toilet conditions. Not keeping the toilet clean is the same as letting germs reproduce in the toilet and are prone to bacteria. Family health is closely related to the cleanliness of the toilet or bathroom. Because the toilet is a nest of various bacteria and germs. Based on these problems, counseling is carried out regarding appropriate technology in making clean and healthy toilets for the wider community. With this counseling and training, the community can improve their healthy lifestyle by using healthy and clean toilets.